AB1296-HPR PREVALENCE OF COMORBIDITIES IN A COHORT OF PATIENTS IN AN EDUCATIONAL MULTIDISCIPLINARY PROGRAM. (2nd June 2020) - Cabrera, M.; Rodriguez, F.; Buitrago-Garcia, D.; Sánchez, G.; Santos-Moreno, P.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory and complex disease. Patients with RA face other diseases that might lead to increase morbidity. In patients with RA it has been stablished a high prevalence of comorbidities and their risk factors (1). Objectives: The aim of this study was to evaluate the prevalence of comorbidities in Colombian patients with RA enrolled in an educational multidisciplinary program and possible correlation with disease activity Methods: We performed a cross-sectional study; we included patients with confirmed diagnosis of rheumatoid arthritis in a specialized RA center. We collected sociodemographic data, and markers of disease activity DAS28. We collected data regarding the history of comorbidities such as hypertension, dyslipidemia, osteoporosis, type 2 diabetes mellitus, hypothyroidism, malignancies, among others. We performed a descriptive analysis, variables with a normal distribution were described using mean and standard deviation (SD), and non- normal distributed variables were described using median and interquartile range. Categorical variables were presented as rates. We evaluated the relationship between disease activity and comorbidities. Results: We included 251 patients; mean age was 59 ± 9.8 years old, with a high proportion of women 93%; median disease duration was 15 years RIQ (8-20); in this study, 145 (65%) of patients were in remission; 35 (11%) had low, 44 (20%) moderate and 10 (4%) high disease activity. Regarding pharmacological therapy, 55% were receiving conventional DMARDs. The prevalence of comorbidities was 85%, the most common were high blood pressure 25% followed by hypothyroidism 12% and diabetes 10%, 0.7% of patients had malignancies such as thyroid cancer or breast cancer, 1.29% of patients had renal comorbidities. Among comorbidities related to RA 30% had osteoporosis and 20% arthrosis. We did not find a statistical association between DAS28 and comorbidities. Conclusion: As other studies have shown, there is a high prevalence of comorbidities among RA patients, mainly high blood pressure. Due to the above, it is relevant to evaluate the risks factors of patients with RA, especially cardiovascular risks. We consider that a multidisciplinary program represents an opportunity not only to educate patients about healthy life styles and the management of RA, but also other diseases in order to increase the empowering of the health status in these poly pathological patients(2). References: [1]Gullick NJ, Scott DL. Co-morbidities in established rheumatoid arthritis. Best practice & research Clinical rheumatology. 2011;25(4):469-83. [2]Galarza-Delgado DA, Azpiri-Lopez JR, Colunga-Pedraza IJ, Cardenas-de la Garza JA, Vera-Pineda R, Wah-Suarez M, et al. Prevalence of comorbidities in Mexican mestizo patients with rheumatoid arthritis. Rheumatology international. 2017;37(9):1507-11. Acknowledgments: This project has been funded by a collaboration between the Ministry of Science, Technology and Innovation COLCIENCIAS (contract 746-2018), the Fundación Universitaria de Ciencias de la Salud and Biomab - Center for Rheumatoid Arthrtitis Disclosure of Interests: Michael Cabrera: None declared, Fernando Rodriguez: None declared, Diana Buitrago-Garcia: None declared, GUILLERMO SÁNCHEZ: None declared, Pedro Santos-Moreno Grant/research support from: I have received research grants from Abbvie, Biopas-UCB, Janssen, Novartis, Pfizer., Speakers bureau: I have been a speaker for Abbvie, Biopas-UCB, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi.